Effect of Holding Time on Density and Morphological Property of Aluminium Composite Using Recycled Materials by Stir Casting Method - Nuhu, Awwal Hussain; Jikan, Suzi Salwah Binti; Asman, Saliza Binti; Badarulzaman, Nur Azam Bin; Zago, Dagaci Muhammad (International Journal of Engineering and Technology, 2018)
Aluminium metal matrix composites were fabricated from recycled materials via stir casting method. The composites differed in their holding time (ht) that is 30 minutes, 45 minutes and 60 minutes accordingly. The microstructures of the composites were analysed using optical microscope as well as scanning electron microscope in order to examine their morphological make-up. The average densities of the composites were determined and compared with one another. There is no significant difference between average densities of the fabricated composites. The observations revealed that varying the ht has greater impact the composites’ morphology, particularly on those composites which have been fabricated at 60 minutes ht.